Analysis of historical and future climatic and hydrologic extremes in the upper Ayerawaddy River Basin in Myanmar - Ghimire, Uttam; Babel, Mukand Singh; Shrestha, Sangam; Tawatchai Tingsanchali; Srinivisan, G.; Thailand (HM King) (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
Several studies across South East Asia point towards Myanmar withincreasingclimatic extremes and impacts associated with those climatic and climate induced extremes. This study dealswith upper part of a major river basin of Myanmar,Ayerawaddy river basin whereassessment of changing climaticand hydrologicextremes and their frequency analysis is done.Dividing the study area into three catchments, 11 sector specific indices of extreme temperature and precipitation and 3 indices of hydrological extremes are analyzed for their trends and return periods under different time periods.A semi distributed calibrated and validated HEC-HMS model is used to simulate daily discharges of historical and future periods under the climate change scenario for whole basin.Three general circulation models (HADGEM2, MIROC5 and GFDL CM3) under CMIP5 are selected based on their suitability to simulate the climatology of study area.The mean stream flowsare impacted in a positive direction under climate change scenarios. Highest increasein mean monthly flows of 275% is simulatedin upper catchment for themonth of April infar future period (2074-2099) under RCP 8.5 scenarioof HADGEM2.The lowest change is approximately 30% during non-monsoon month of November in early future period of RCP 4.5 of GFDL.Mean decadal change is also projected to have a maximum increase of 132% during end of 21stcentury as simulated by RCP 8.5 scenario of HADGEM2.The analysis oftemperature related extremes reveal a significant increase in hot extremes and drastic reduction in cold extremes across all catchments.The frequency of hot temperature extremes have increased prominently for all catchments, with more prominence in upper part of study area. RCP 8.5 scenario with significant increase in climatic extremes compared to RCP 4.5, simulated frequent rainfall extreme events.Under future scenarios, mean ensemble is projecting decrease in drought conditions in all catchments, represented byclimatic and hydrologic indicators. Individual GCMs showa mixture of changes while simulating dry days. RCP 4.5 is simulating drier extremes compared to RCP 8.5 for all catchments. The frequency of higher rainfall related extremesand annual maximum flows under future time slices indicate frequent flooding in the catchment. No rain episodes as an indicator of meteorological drought and minimum flow indices as indicator of hydrological droughtreveals insignificant drought persistence under RCP 4.5 scenario. The results are useful to understand the potential changes in frequency of extreme climatic and hydrologic events and can be incorporated to formulate impact assessment and thus the adaptation strategies to reduce the losses and negative effects of such extreme events in different sectors.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering inWater Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2016
Keywords: Climatic change -- Ayerawaddy River Basin (Myanmar); Hydrological forecasting -- Ayerawaddy River Basin (Myanmar)